PERCEPTION OF PUBLIC HOSPITALS AT MALANG RAYA IN THE APPLICATION OF GREEN ACCOUNTING - Ashari, Muhammad Hasyim; Mustapa, Gusnar (JEA17: Jurnal Ekonomi Akuntansi, 2022)
The aim of this study is to determine the perception of public hospitals in the area of MalangRaya in relation to the application of green accounting. The approach in this survey researchuses descriptive quantitative. 35 samples from 40 population groups of public hospitals are likelyto be obtained by distributing questionnaires which calculated the average value of eachexplanation to be interpreted and closed. The conclusion of this study shows that the perceptionof public hospitals regarding the use of green accounting in public hospitals in Malang Raya,based on respondents' responses, shows that public hospitals agree to the use of greenaccounting based on financial activities, social activities and environmental activities. Thelimitation of the study is that it is difficult to obtain responsive data due to procedures andbureaucracy, as well as differences in the position, position and level of education ofrespondents, which can lead to different perceptions of the use of green accounting in publichospitals. The results of this study are expected to provide guidance on how to regulate greenaccounting in public hospitals